Interaction of Macroeconomic Models of Mundell and Fleming: Historical Aspect - Yevhenii ALIMPIIEV (Communications of International Proceedings, 2022)
The paper investigates the logical and chronological sequence of development of models of interaction between financial and monetary policies. Models that were developed independently by two scientists, Mundell and Fleming, are considered, and on the basis of which, in the process of evolution of independent approaches of scientists to improve their models and as a result of the convergence of the results obtained, the modern Mundell-Fleming model was proposed to explain the macroeconomic effects of the interaction of financial and monetary policy in an open economy. The findings can be useful for further development of models explaining the possibilities of interaction between financial and monetary authorities in order to influence the macroeconomic balance, as well as for didactic purposes.
Keywords: fiscal and monetary policy; simple Keynesian model; Mundell-Fleming model; IS-LM-BP model